(untitled) (Scientific journal of the Fergana State University, 2024)
In language learning, many aspects of language develop slowly. In Language Teaching one of the serious problems is with which methods and techniques the language is carried out related. Another problem is that in school’s foreign languages are in low hours teaching. To speak, read, write, listen and understand and increase vocabulary and to apply these correctly, it is necessary to effectively conduct classes for 6-7 years there must be educational programs and subjects that are intended. From this we think, there are not enough foreign languages that take place in a week.